2020
DOI: 10.1109/access.2020.3028831
|View full text |Cite
|
Sign up to set email alerts
|

MEG Sensor Selection for Neural Speech Decoding

Abstract: Direct decoding of speech from the brain is a faster alternative to current electroencephalography (EEG) speller-based brain-computer interfaces (BCI) in providing communication assistance to locked-in patients. Magnetoencephalography (MEG) has recently shown great potential as a non-invasive neuroimaging modality for neural speech decoding, owing in part to its spatial selectivity over other high-temporal resolution devices. Standard MEG systems have a large number of cryogenically cooled channels/sensors (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 87 publications
(97 reference statements)
1
15
0
Order By: Relevance
“…We also found that the beta-band stood out as a prominent feature in the neural encoding of imagined speech, both in terms of power and CFC (low-beta/gamma and low-beta/BHA), with slightly better performance when using power. This finding aligns well with the notion that the beta band plays an important role in endogenous processes, notably in relation with top-down control in the language domain 16 , 17 , 40 , 43 , 48 , 49 . Although repeating a heard or written word engages automatic, almost reflex, neural routines, imagined speech is a more voluntary action requiring enhanced endogenous control from action planning frontal regions 50 52 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that the beta-band stood out as a prominent feature in the neural encoding of imagined speech, both in terms of power and CFC (low-beta/gamma and low-beta/BHA), with slightly better performance when using power. This finding aligns well with the notion that the beta band plays an important role in endogenous processes, notably in relation with top-down control in the language domain 16 , 17 , 40 , 43 , 48 , 49 . Although repeating a heard or written word engages automatic, almost reflex, neural routines, imagined speech is a more voluntary action requiring enhanced endogenous control from action planning frontal regions 50 52 .…”
Section: Discussionsupporting
confidence: 90%
“…Imagined speech decoding with non-invasive techniques, i.e. surface electroencephalography (EEG) or magnetoencephalography (MEG), has so far not led to convincing results, despite recent encouraging developments (vowels and words decoded with up to ~70% accuracy for a three-class imagined speech task) [12][13][14][15][16][17] . The most effective approach so far to advance toward a real "imagined speech" decoding system is based on electrocorticographic (ECoG) signals, which are currently only recorded in patients with refractory epilepsy undergoing presurgical evaluation.…”
mentioning
confidence: 99%
“…In Dash et al [29], they proposed the forward selection algorithm using spatial selectivity of MEG signals. The aim of this study is to minimize the number of sensors for neural speech decoding.…”
Section: A Feature Extractionmentioning
confidence: 99%
“…Furthermore, Dash et al [32] this is limited to practical use in real BCIs due to their high price, large size and weight [29]. Cooney et al [33] used independent component analysis with Hessian approximation preconditioning to eliminate electrooculography signals.…”
Section: B Classifier Trainingmentioning
confidence: 99%
“…The distribution of the modalities used for decoding imagined speech in these papers is given in Figure 1 . These modalities include EEG, ECoG (Herff et al, 2015 , 2016 ), fMRI (Yoo et al, 2004 ; Abe et al, 2011 ), fNIRS (Herff et al, 2012 ; Kamavuako et al, 2018 ; Sereshkeh et al, 2018 ), MEG (Destoky et al, 2019 ; Dash et al, 2020 ), ICE (Brumberg et al, 2011 ; Kennedy et al, 2017 ; Wilson et al, 2020 ) etc. Clearly, EEG is the most popular modality used for decoding imagined speech with 18 articles using it for capturing the neural changes during imagined speech.…”
Section: Introductionmentioning
confidence: 99%